Increasing the level of speed-strength training of football players 17-18 years old - Vladimir Perevoznik; Volodymyr Paievskyi (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to develop sets of exercises for the development of speed-strength preparedness of student football players 17-18 years old and experimentally verify the effectiveness of their use. Materials and methods: analysis of scientific and methodological literature, pedagogical testing of indicators of speed-power qualities, pedagogical experiment, methods of mathematical statistics. The study involved 24 footballer-student of KhGAFK, which were divided into two groups, experimental and control, 12 athletes each. Results. After the introduction of the experimental methodology, a positive dynamics was found in the indicators of speed-strength preparedness of football players aged 17-18 years of the experimental group. Findings. The level of development of speed-power qualities in the experimental and control groups increased, but the best indicators were in the experimental group. So, the average long jump from the place of the experimental group was 264.9 ± 2.10 cm, and in the control - 260.4 ± 2.31 cm (t = 3.51; P <0.001), a five-fold jump in the experimental group -1307.3 ± 3.82 cm in the control group - 1281.2 ± 6.92 cm (t = 5.29; P <0.001), uphill jump from a place in the experimental group 52.3 ± 0.64 cm, in the control group, 49.9 ± 0.51 cm (t = 6.4; P <0.001).